Ethics Committees in Hospitals - Spagnolo, Antonio (Medicina e Morale, 2024)
In the face of the increasing technicalisation of medicine, increasingly daring experimentation, especially in the initial and terminal phases of life (on embryos, on the terminally ill), and the dehumanisation of the hospital structure, there is a widespread need to bring the field of biomedical sciences back to a human scale by setting up committees that can somehow safeguard the fundamental purpose of medicine, which is to cure man and defend his dignity as a subject during the healing process itself.